Fyodor Dostoevsky : the gathering storm (1846-1847) : a life in letters, memoirs, and criticism - Marullo, Thomas Gaiton (NIU series in Slavic, East European, and Eurasian studies., 2020)
"The second volume in a three-part work on the young writer, this diary-portrait of Dostoevsky's early years is drawn from the letters, memoirs, and criticism of the writer, as well as from the testimony and witness of family and friends, readers and reviewers, and observers and participants in his life"--Provided by publisher